Differentiated Instruction Approach to Overcoming Heterogeneity in Initial Nahwu Ability of New Students in Arabic Language Education Study Program - Joni Kawijaya; Yusuf Mustofa; Khabibul Khoiri (Innovate Inovation Teaching And Learning, 2026)
Nahwu instruction in Islamic higher education faces challenges from heterogeneous student abilities and conventional teaching methods. This study analyzes Differentiated Instruction in addressing diverse initial nahwu skills among Arabic Education students at IAI Darul A'mal Lampung and measures its effectiveness. Using a qualitative case study with 32 participants, data were collected via diagnostic tests, observations, and interviews, then analyzed using the Miles and Huberman model. Findings indicate significant improvement, with average scores rising from 62.3 to 78.6. Approximately 84% of students showed significant progress, particularly those with low initial abilities, highlighting the effectiveness of content differentiation. Furthermore, process and product differentiation enhanced student engagement and motivation. The study concludes that Differentiated Instruction effectively creates adaptive, inclusive learning environments. Consequently, developing differentiated strategies and materials is essential for improving Arabic language learning quality in higher education.